Evaluación para la obtención de almidón aprovechando los residuos de mango (Mangifera Indica L.) Para la producción de un biopolímero (2021)
The present research project aims to produce a biopolymer from the extraction of starch in mango (Mangifera Indica L.) residues. In this way, a bibliographic compilation was made, where the characteristics and properties of biopolymers, starch and mango as raw material are studied. In addition, key information related to the formation of a biopolymer from mango starch is presented. Once all the information has been collected, the most important methodology, parameters and variables for the starch extraction process are identified.